Recombinant Trichinella pseudospiralis Serine Protease Inhibitors Alter Macrophage Polarization In Vitro - Xu, Ning; Liu, Xiaolei; Tang, Bin; Wang, Libo; Shi, Hai N.; Boireau, Pascal; Liu, Mingyuan; Bai, Xue (Frontiers in Microbiology, 2017)
During parasite infection, serine protease inhibitors secreted by parasites play important roles in suppressing host defenses. However, the mechanism of immune regulation is unclear. In this study, a serpin gene from Trichinella pseudospiralis, named Tp-Serpin, was cloned and expressed, in order to reveal its role in the regulation of the host immune response in T. pseudospiralis infection. The results showed that Tp-Serpin encodes a 43kDa protein that was recognized by serum from T. pseudospiralis infected mice at 60 days post infection (dpi). Tp-Serpin was found to be expressed at all developmental stages of T. pseudospiralis. Inhibitory activity analysis showed that recombinant Tp-Serpin (rTp-Serpin) effectively inhibited the hydrolytic activity of porcine pancreatic elastase (elastase P), human neutrophil elastase (elastase H) and mouse mast cell protease-1 (mMCP-1), but showed little inhibitory for human neutrophil cathepsin G (cathepsin G). Furthermore, rTp-Serpin induced polarization of macrophages towards the alternatively activated phenotype (M2) alone by activation of the signal transducer and activator of transcription 3(STAT3) signaling pathway, and inhibited LPS-induced classically activation (M1) in vitro. These data preliminarily demonstrate that Tp-Serpin may play an important role in the immunoregulation of T. pseudospiralis infection by activating the M2-polarized signaling pathway.